2019
DOI: 10.1101/761791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The consequences of mixed-species malaria parasite co-infections in mice and mosquitoes for disease severity, parasite fitness, and transmission success

Abstract: The distributions of human malaria parasite species overlap in most malarious regions of the world, and co-infections involving two or more malaria parasite species are common. Little is known about the consequences of interactions between species during co-infection for disease severity and parasite transmission success. Anti-malarial interventions can have disproportionate effects on malaria parasite species, and may locally differentially reduce the number of species in circulation. Thus, it is important to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…It is also possible that in symptomatic P. falciparum infections, this species competitively excludes co-infecting species due to increased parasitaemia. This exclusion could result from within-host competition for resources (66). Or through host-immune mediated mechanisms in which the innate immune response triggered by the high parasitaemia P. falciparum disproportionately affects the less dominant of the species in the co-infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that in symptomatic P. falciparum infections, this species competitively excludes co-infecting species due to increased parasitaemia. This exclusion could result from within-host competition for resources (66). Or through host-immune mediated mechanisms in which the innate immune response triggered by the high parasitaemia P. falciparum disproportionately affects the less dominant of the species in the co-infection.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of mixed P. malariae and P. falciparum co-infections was much higher in asymptomatic compared to symptomatic parasite carriers, the latter of which were almost exclusively infected with single species P. falciparum . Interactions between malaria parasite species can have profound impacts on the severity of disease (Tang et al, 2019). This observation is consistent with those of Black et al (1994), who found 27-32% of asymptomatic children under nine years old in the Ivory Coast harboured mixed P. falciparum and P. malariae infections, while no mixed infections were observed in symptomatic children (Black et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of P. malariae co-infection in symptomatic patients may be caused by the overgrowth of one or more clones of P. falciparum . This could have lead to the competetive exclusion of P. malariae either through within host-competition for host blood cells (Tang et al, 2019), or through the raising of an acute inate immune response in the host that kills off the slower growing species (Molineaux et al, 1980). Supporting this is our observation that the multiplicity of P. falciparum infection in symptomatic patients is significantly lower than in asymptomatic parasite carriers.…”
Section: Discussionmentioning
confidence: 99%
“…7 Plasmodium species occur sympatrically globally and as simultaneous infections in host and vectors, but their salient biology sustains their species distinctiveness. Studies on mixed Plasmodium species biology suggest that interactions between co-infecting Plasmodium species shape infection dynamics, virulence, 8 species frequency due to altered resource allocation, 9 and the response of each species to both human host and vector immunity. Some studies associate these interactions with preventing development of severe malaria disease 10 and modulating transmission 8,11,12 for certain species in an infection.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on mixed Plasmodium species biology suggest that interactions between co-infecting Plasmodium species shape infection dynamics, virulence, 8 species frequency due to altered resource allocation, 9 and the response of each species to both human host and vector immunity. Some studies associate these interactions with preventing development of severe malaria disease 10 and modulating transmission 8,11,12 for certain species in an infection. Mixed Plasmodium species infections pose an intervention challenge due to the variability in case management and transmission prevention.…”
Section: Introductionmentioning
confidence: 99%